Virtual Democracy: Online Ballet and Contemporary Dance Classes During the Covid-19 Crisis - Milovanovic, Dara (The International Journal of Screendance, 2021)
This article considers the politics and dynamics of online ballet and contemporary dance classes during the Covid-19 lockdown on geo-political, economic, and cultural implications of dance classes in digital media. Using a post-colonial lens and popular dance studies, this research analyzes the effect of the online ballet and contemporary classes colonizing digital spaces and the effect of this phenomenon on creating a more democratic and participatory access to dance that has built a more global and inclusive engagement with the arts for geographically peripheral spaces. This essay investigates the kind of common created by kinaesthetic experience of the dancers teaching and participating in the classes in digital media providing a key strategy to analyze the participatory embodiment of dancers as a radical, material, corporeal challenge to the hierarchies of the dance world, and furthermore, the economic dynamics that shape it.